Tradisi Ngirim Banyu di Sumber Genitri Desa Claket Kecamatan Pacet Kabupaten Mojokerto - Samroatul Sa’adah; Ananda Syaifullah Firman Fathani (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Javanese culture is a product of the community’s collective thought, expressed through traditions that have been preserved over generations. However, cultural practices may face decline due to the pressures of modernization and changing times. Therefore, efforts to preserve and sustain cultural heritage are essential. One method of cultural transmission is through traditional practices. The Ngirim Banyu tradition at Sumber Genitri, Claket Village, represents a form of semi-oral folklore that is still regularly performed by the local community in Claket Village, Pacet District, Mojokerto Regency. This tradition is carried out as an expression of gratitude to God Almighty for the blessings received, particularly the natural spring that sustains the village. This study aims to explore the origins, procedures, ritual components (ubarampe), symbolic meanings, functions, transformations, and preservation efforts related to the Ngirim Banyu tradition at Sumber Genitri. The research also seeks to broaden the researcher’s perspective, knowledge, and experience concerning the existence of local traditions. The theoretical framework used in this study includes concepts of folklore, symbolism and meaning, belief systems, cultural functions, cultural change, and cultural preservation strategies.